Sistem Informasi Penjualan Makanan Secara Online Di RM Sedep Roso Rantauprapat Berbasis Web - Elfrida, Sartika (Universitas Labuhanbatu, 2021)
The Sedep Roso Restaurant is a restaurant that sells food menus and now the restaurant still uses a manual system on its sales or data management. In a system called manual such as using stationery, ordering process, making invoices, sending process to buyers. Therefore it takes a long time to manage the data. And so the restaurant needs an information system that can later help the restaurant in the sale or management of data that can overcome if there are obstacles. This restaurant aims to build an application or ordering information system at a web-based restaurant with implementation using localhost and design that uses a unified modeling language (UML) model. With the existence of these systems that can be expected at the Restaurant Employees can manage applications that have been made to manage sales of Food Menu data such as food menu ordering reports.